Manajemen Pembelajaran Pendidikan Agama Islam dalam Membentuk Akhlakul Karimah Siswa - Putri Susilawati; Lukman Asha; Ifnaldi Ifnaldi; Jumira Warlizasusi (Journal of Education and Instruction (JOEAI), 2022)
This study aims to describe how planning, organizing, implementing and evaluating the learning management of Islamic Religious Education (PAI) in shaping the morals of students at SMPIT Khoiru Ummah Rejang Lebong. This research is a qualitative research in the form of developmental research, using interviews and observations to obtain data. The results of this study indicate that; First, learning management includes planning (Planning), organizing (organizing), implementation (actuating), evaluation (Controlling) in the good category, carried out on the basis of religious thinking and then developed at SMPIT by practicing religious values ​​that are believed and carried out in daily life. -day, and is carried out by utilizing additional hours in extracurricular activities. Second, the implementation pattern of PAI learning management is very unique, such as the application of religious culture at SMPIT Khoiru Ummah Rejang Lebong through the culture of greetings, excuses, sorry and thank you, and complete reading and writing of the Koran, dhuha prayer, dhuhur prayer in congregation, istighosah and joint prayer, commemoration of Islamic holidays, imtaq and tadarrus al-Qur'an activities, prayer together at the beginning and end of lessons, handshakes between school members, and the use of Muslim and Muslim clothing. In conclusion, PAI learning management in shaping the morals of students at SMPIT Khoiru Ummah starts from planning (planning), organizing (organizing), implementing (acting), and evaluating (Controlling) all of which are in the good category to shape the morals of students through planting activities. -activities and application of religious culture. Keywords: Student Morals, Learning Management